The Electronic and Transactions Law (EIT Law) as the First Cybercrime Law in Indonesia: An Introduction and Its Implementation - Mahrina Mahrina; Joko Sasmito; Candra Zonyfar (Faculty of Law, Universitas Pekalongan, 2022)
The cybercrime cases across the country are remaining high. It caused the government decided to create the cybercrime law, including the Indonesian government. The first cybercrime law that created by Indonesian government is the Electronic and Transactions Law (EIT Law) of 2008, and revised in 2016. This paper then provides more comprehensive explanation regarding EIT Law, starting from its creation, substances, enforcement, and even its strengths and weaknesses. By using literature review method, the authors have been conducted research from the previous studies on related topic. Before entering the main discussions, this paper also explains the cybercrime law and policy in Indonesia’s neighboring countries. After that, EIT Law is explained comprehensively. The result shows that background of the creation of EIT Law is the technology and the Internet development that can threaten the Indonesia’s national interests. This law then categorize the types of cybercrime that prohibited in Indonesia. The jurisdiction, the investigation process, and the punishment to cyber criminals also regulated in that law. Furthermore, this paper also explains the strengths and weaknesses of EIT Law. The strengths of EIT Law can be seen in the complexity of the articles that contain within it. Nevertheless, the implementation of this law is still not effective. This is because there are several issues that have to corrected, such as the ambiguity of article contents, lack of cybercrime awareness among the law enforcement officers, difficulties to provide electronic devices, and lack of cyber facilities or infrastructure. Keywords: Cybercrime, Cyberspace, EIT Law, National interest, Technology and internet development